Projeto - Da emoção de ler a descoberta do prazer - Verão, Silvana Pedrosa; Cardoso, Edilene Jesus; Oliveira, Maria das Graças Alves; Vieira, Maria Suerlanda; Barbosa, Roseli dos Reis; Polli, Vanderley Gomes; Foresti, Nelci Nogueira; Oliveira, Maria Auxiliadora; Souza, Marlene Alves; Simião, Regina A. Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF